Research Note: Injection of adenoviral CRISPR/Cas9 system targeting melanophilin gene into different sites of embryos induced regional feather color changes in posthatch quail - Joonbum Lee; Dong-Hwan Kim; Kichoon Lee (Poultry Science, 2023)
ABSTRACT: Poultry species is an important animal model in both avian research and the poultry industry. To advance our understanding of genetic factors and benefit both fields, a gene of interest can be genetically edited, and consequential phenotypic changes can be investigated. Injection of adenovirus containing the CRISPR/Cas9 system into avian blastoderm induced genome editing in blastodermal cells randomly, including primordial germ cells, which results in generation of whole-body knockout in the offspring of the virus-injected quail. However, to observe phenotypic and functional changes in whole-body, homozygous knockout of genes using this genome editing technology requires at least 2 generations of breeding of chimeric, and heterozygotes birds. In the current study, we developed a strategy to investigate the gene function in 1-generation by inducing regional genome editing around the injection sites with CRISPR/Cas9 adenovirus. The adenoviral CRISPR/Cas9 vector targeting the melanophilin (Mlph) gene, regulating feather pigmentation, was injected into 2 different regions of embryos, the cervical flexure of quail embryos at HH stage 13 to 15 and the tip of the upper limb bud of embryos at HH stage 22 to 24, to induce genome editing in those regions. Indel mutations in the target loci of the Mlph gene were detected by extracting genomic DNA from the embryonic tissues, and consequential phenotypes, feather color changes, were analyzed at 1 mo after hatch. Injection of the adenovirus into the cervical flexure and the tip of the upper limb bud of embryos resulted in 8 to 21% efficiency of indel mutation in the embryonic cells of the injected regions. In the posthatch quail, gray feathers were shown on their upper back and primary wing feathers, corresponding to the injection sites at embryos. Successful validation of this strategy for inducing genome editing in parts of tissues within 1-generation will accelerate studies on genetic functions with advantages of less time and cost, facilitating avian research and providing foundations for future application for the poultry industry.